PENINGKATAN KEMAMPUAN GURU DALAM MENGEMBANGKAN RANCANGAN PERMASALAHAN MATEMATIKA DITINJAU DARI LEVEL KEMAMPUAN BERPIKIR SISWA - Baiq Rika Ayu Febrilia; Eliska Juliangkary (KALAMATIKA Jurnal Pendidikan Matematika, 2019)
The ability of a teacher to design mathematical problems affects the characteristics and quality of mathematics learning that teachers do in class. Therefore, teachers need to have insight into how to design problems to encourage certain students' thinking skills. This study aims to describe improvement in teacher's ability to design mathematics problems before and after discussion activities designed by researchers. The method used is qualitative descriptive with the subject of seven junior high school mathematics teachers. Based on the results of this study it was found that after participating in the discussion activities, the number of teachers who designed problems that could encourage the level of thinking ability to apply decreased by 28.57%, the level of evaluation increased by 21.43%, the level analyzed remained, and the level of understanding increased by 7.14%. From 28 problems that have been designed both before and after the discussion activities, it is found that 10.71% is a matter that drives the level of understanding, 50% encourages the level of application, 17.86% encourages the level of analysis and 21.43% encourages the level to evaluate.